2018
DOI: 10.1101/265512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide analysis of adolescent psychotic experiences shows genetic overlap with psychiatric disorders

Abstract: This study aimed to test for overlap in genetic influences between psychotic experience traits shown by adolescents in the community, and clinically-recognized psychiatric disorders in adulthood, specifically schizophrenia, bipolar disorder, and major depression. The full spectra of psychotic experience domains, both in terms of their severity and type (positive, cognitive, and negative), were assessed using self-and parent-ratings in three European community samples aged [15][16][17][18][19]098). A megagenome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…Heritability estimates of schizophrenia are considerably higher than of PENS in the community (80% versus 30-50%, respectively) (23,41) but it is not a like for like comparison because the schizophrenia estimate assumes an underlying liability. While the question of a qualitative cut off is not settled, as discussed below in our systematic review, genome-wide studies have considerably advanced our understanding of the link between psychiatric conditions and PENS through estimating shared genetic variance using measured DNA variants (1,3,4,(42)(43)(44)(45)(46)(47).…”
Section: Psychotic Experience and Negative Symptom Traits (Pens) And ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Heritability estimates of schizophrenia are considerably higher than of PENS in the community (80% versus 30-50%, respectively) (23,41) but it is not a like for like comparison because the schizophrenia estimate assumes an underlying liability. While the question of a qualitative cut off is not settled, as discussed below in our systematic review, genome-wide studies have considerably advanced our understanding of the link between psychiatric conditions and PENS through estimating shared genetic variance using measured DNA variants (1,3,4,(42)(43)(44)(45)(46)(47).…”
Section: Psychotic Experience and Negative Symptom Traits (Pens) And ...mentioning
confidence: 99%
“…The number of papers identified by looking through reference lists was 0. Three other studies were identified by the authors through reading unpublished manuscripts on Biorxiv or from being involved in the work or citing the studies (1,48,49), making a total of 13 studies. Results were summarized in a table form.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with models of developmental etiology and pathogenesis of diseases, our framework first acknowledges the associations between psychotic experiences and chronic conditions may be explained by shared underlying genetic liabilities. Psychotic experiences are moderately heritable (Ronald et al, 2014;Sieradzka et al, 2015) and overlap partly with chronic health conditions (Legge et al, 2019;Pain et al, 2018; and health behaviors (Taylor et al, 2015). The persistence of psychotic experiences (which may be especially predictive of health problems) can be attributable to some common genetic factors as well (Wigman et al, 2011).…”
Section: Genetic Predispositionmentioning
confidence: 99%